Probability of Anti PDGF/R as Antiangiogenic Nasopharyngeal Carcinoma: A Review - Oke Kadarullah (TALENTA PUBLISHER, 2020)
Introduction: Nasopharyngeal Carcinoma (NPC) is frequently found in Southeast Asia, especially in Indonesia, with a higher incidence rate compared to global numbers. The mortality rate of NPC in Indonesia is also higher than the standardized mortality rate. Radiotherapy and chemotherapy are the first line treatment, but still has 5 – 10% chance of recurrence. NPC is mostly persistence and recurrence, and this itself is a challenge in achieving effective treatment. Patients in Indonesia commonly search for treatment at an advanced stage. Review: Advanced stage NPC requires an additional combination therapy such as chemotherapy and targeted therapy. Targeted therapy in the past 10 years have not shown a significant improvement in recurrent NPC. Cetuximab is the empiric choice for head and neck squamous cell carcinoma. EGFR and VEGFR are target molecules tyrosine kinase, including PDGF/R, which plays a role in angiogenesis and cancer progressivity. PDGF and its receptors shows an important role in certain cancers including head and neck cancer. PDGF/R in NPC has been researched in vitro and in vivo but more clinical data is still needed. Conclusion: The role of PDGF/PDGFR in targeted therapy development is still being used. This is to push the anti angiogenic combination strategy as an option for NPC with radio-chemotherapy resistance, or for stable, progressive and recurrent NPC while considering its unwanted effects.